Vancomycin-Resistant Enterococci - Cetinkaya, Yesim (American Society for Microbiology, 2000)
After they were first identified in the mid-1980s, vancomycin-resistant enterococci (VRE) spread rapidly and became a major problem in many institutions both in Europe and the United States. Since VRE have intrinsic resistance to most of the commonly used antibiotics and the ability to acquire resistance to most of the current available antibiotics, either by mutation or by receipt of foreign genetic material, they have a selective advantage over other microorganisms in the intestinal flora and pose a major therapeutic challenge. The possibility of transfer of vancomycin resistance genes to other gram-positive organisms raises significant concerns about the emergence of vancomycin-resistant Staphylococcus aureus. We review VRE, including their history, mechanisms of resistance, epidemiology, control measures, and treatment.